Ischemic stroke in neonatal and adult astrocytes. (October 2019) - Revuelta, Miren; Elicegui, Amaia; Moreno-Cugnon, Leire; Bührer, Christoph; Matheu, Ander; Schmitz, Thomas
Highlights: Neonatal and adult astrocytes activate distinct mechanisms after stroke. Time course of glial activation is strongly age dependent. Reactive astrocytes could represent a potent target for stroke recovery. Abstract: The objective of this paper is to review current information regarding astrocytes function after a stroke in neonatal and adult brain. Based on the current literature, there are some molecular differences related to blood brain barrier (BBB) homeostasis disruption, inflammation and reactive oxygen species (ROS) mediated injury between the immature and mature brain after an ischemic event. In particular, astrocytes, the main glial cells in brain, play a different role in neonatal and adult brain after stroke, as time course of glial activation is strongly age dependent. Moreover, the present review provides further insight into the therapeutic approaches of using neonatal and adult astrocytes after stroke. More research will be needed in order to translate them into an effective treatment against stroke, the second main cause of death and disability worldwide.